EDUKASI KESEHATAN DAN PROMOSI KEGIATAN LEMBAGA TAHFIDZ BAITUL QUR’AN DALAM UPAYA PENCEGAHAN PENYALAHGUNAAN NARKOBA DI KELURAHAN SURAU GADANG KOTA PADANG - Syafrawati syafrawati; Shelvy Haria Roza; Nia Oktavina; Sindi Maulani (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Nanggalo is vulnerable to social problems such as juvenile delinquency. Juvenile delinquency cases such as drug abuse, theft often occur around Surau Gadang Village, Nanggalo. One of the factors that cause delinquency is the lack of moral education. One of the qualified moral education is the religious approach. One of the religious institutions is the house of tahfiz Al-Qur'an. Based on the results of interviews with local RT officials, it was found that there had never been counseling about drugs in the area. In addition, there is a tahfidz institution as a means of preventing drug abuse, but the number of students is still minimal due to lack of promotion. The purpose of this community service is to increase the knowledge of teenagers about drugs and increase the promotion of the tahfidz house. Community service uses health promotion methods by distributing anti-drug flyers, education about drug prevention to teenagers and promoting the Baitul Qu'ran tahfidz house. The activity was carried out at the Raya Nanggalo Mosque and Al-Qadar Mosque. The results of this community service show that there is an increase in adolescent knowledge before and after being given counseling about drugs. Around 49 teenagers in Surau Gadang Village have been exposed to information about the existence of the Baitul Qur'an tahfidz house. It is hoped that in the future the promotion of the Tahfidz house can be carried out more broadly, such as using social media.